KEPERCAYAAN PADA PEMIMPIN UPAYA MENINGKATKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Ahmad Ahmad (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2021)
Low employee work behavior makes the Village Government in Lebak Regency to determine appropriate and strategic steps, the research objective is to find factors that influence organizational membership behavior or organizational citizenship behavior through testing the direct influence of ethical leaders and trust in leaders, Research approach using quantitative surveys of the total population of 1,700, 319 samples were used from the Village Apparatus in Lebak Regency. Found a direct influence of ethical leaders and trust in leaders on organizational citizenship behavior. The results show that leaders in the Village Government must improve ethics and trust in leader-members so that it has implications for the behavior of organizational membership to make their best achievements that can contribute well to the organization.